Determining the alumina solubility in low-temperature KF-NaF-AlF3 melts using electrochemical methods - Sai Krishna Padamata; Daniel Gunnarsson; Rauan Meirbekova; Andrey Yasinskiy; Gudrun Saevarsdottir (Results in Chemistry)
Alumina solubility in KF-NaF-AlF3 melt was estimated using square wave voltammetry and linear sweep voltammetry methods. A 45° inclined and horizontal electrode were used in square wave voltammetry and linear sweep voltammetry, respectively. The electrolyte used in this study had a cryolite ratio (CR) of 1.3 and a potassium ratio (KR) of 0.3 at 800 °C. Voltammograms were recorded on both electrodes at different alumina concentrations in the melt. Based on these studies, the alumina solubility in the studied melt is 3.879 wt%, which agrees with the literature.